Prevention Strategies of Prehypertension among Adolescents in Developing Countries: A Scoping Review - Annisa Novanda Maharani Utami; Bagoes Widjanarko; Zahroh Shaluhiyah (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Adolescents in developing countries face a significant risk of prehypertension, with prevalence rates varying across different regions. In Indonesia, 16.8% of adolescents aged 15-19 have prehypertension. Several factors contribute to prehypertension in adolescents, including lifestyle choices, genetics, and environmental factors. Preventing prehypertension in adolescents is crucial for promoting their overall health and reducing the risk of future cardiovascular diseases. This study aims to determine the prevention strategies to reduce prehypertension among adolescents in developing countries. Methods: This scoping review followed PRISMA-ScR guidelines. Articles were retrieved from PubMed, Science Direct, and ProQuest using predefined keywords. The search, conducted between March and June 2024, focused on studies published in the last five years (2019–2024). Results: The search yielded 2,425 articles (712 from PubMed, 1,597 from Science Direct, and 116 from ProQuest). After screening and eligibility assessment, 10 relevant studies were selected. These studies identified key prevention strategies, including health education, dietary modifications (DASH diet), physical activity, and stress management. Conclusion: A multifaceted approach is crucial for preventing prehypertension among adolescents. School-based interventions are the most evidence-based and feasible in resource-limited settings, offering broad coverage and lower costs. Clinicians should support blood pressure screening and nutrition education, while educators should integrate health topics into curricula and encourage physical activity. Policymakers should expand school-based health programs and support further research. Community-based programs are also essential for reaching out-of-school adolescents, making both approaches complementary in prehypertension prevention.